The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/nau.22781
|View full text |Cite
|
Sign up to set email alerts
|

Do ultrasound findings of levator ani “avulsion” correlate with anatomical findings: A multicenter cadaveric study

Abstract: There is a clear difference between anatomical and USS findings. The imaged appearance of an "avulsion" does not represent a true anatomical "avulsion" as confirmed on dissection. The term "avulsion" is misrepresentative and should not be used to describe this imaging finding. Moreover, further attempts at surgically repairing this defect should be avoided, at least until there is a better understanding of its pathophysiology. Neurourol. Urodynam 35:683-688, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…This selection could introduce bias into the CNN, challenging the development of such a method capable of dealing with avulsions, based on these limited data. Avulsion of the PRM influences its appearance on TPUS and there is no complete agreement between experts on the appearance of avulsions. Therefore, we decided to focus on the intact pelvic floor by including only the data of nulliparae in our training set.…”
Section: Discussionmentioning
confidence: 99%
“…This selection could introduce bias into the CNN, challenging the development of such a method capable of dealing with avulsions, based on these limited data. Avulsion of the PRM influences its appearance on TPUS and there is no complete agreement between experts on the appearance of avulsions. Therefore, we decided to focus on the intact pelvic floor by including only the data of nulliparae in our training set.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may explain our findings showing the association between menopause and defective involuntary PFM contraction. Impaired PFM contractions during sudden increases in the intra‐abdominal pressure may relate to levator avulsion or attenuation, which is linked to weaker pelvic support represented in the postmenopausal women in the present study. Weaker PFM contractions may also be associated with reductions in the vascularization and volume of the levator ani muscle as well as increased noncontractile tissue (intramuscular fat) after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we have found that “avulsions” are associated with a narrowing of the PVM attachment depth . This may be the anatomical finding which is visible on MRI 28 , in delivery suite 29 , in the operating theatre and on clinical examination .…”
mentioning
confidence: 63%
“…There was 100% (perfect) agreement for the presence or absence of an anatomical “avulsion”. In fact, there was not a single ultrasonographically observed “avulsion” seen on anatomical dissection …”
mentioning
confidence: 99%